PERAN HUMAS DALAM MENINGKATKAN CITRA POSITIF SEKOLAH SMK TRIYADIKAYASA AEK SONGSONGAN - Mulia Suci Ramadani; Muhammad Alfikri (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
The image of educational institutions, formed based on various components, including academic or academic reputation can be done by improving the professional performance of school principals, teachers and related staff in schools, having a good organizational network for teachers and parents, as well as a clear curriculum to create graduates. which is good too. The method used in this research is a qualitative approach. The data sources that can be used in research are based on data sources, while the research results show that: 1) The role of public relations in improving the quality of education through internal and external activities. Public relations is always assisted by teachers and principals, because public relations cannot stand alone. 2) Supporting factors in building the school's image through public relations performance planning, public relations performance implementation and public relations performance evaluation.